2023
DOI: 10.1186/s13054-023-04586-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent diabetes and long-term cardiovascular outcomes in adult sepsis survivors: a population-based cohort study

Federico Angriman,
Patrick R. Lawler,
Baiju R. Shah
et al.

Abstract: Background Sepsis survivors are at elevated risk for cardiovascular disease during long-term follow-up. Whether diabetes influences cardiovascular risk after sepsis survival remains unknown. We sought to describe the association of diabetes with long-term cardiovascular outcomes in adult sepsis survivors. Methods Population-based cohort study in the province of Ontario, Canada (2008–2017). Adult survivors of a first sepsis-associated hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Similarly, a large Chinese nationwide population-based cohort study showed that patients with T2DM more frequently develop acute kidney injury (AKI) and require renal replacement therapy (RRT), but this was not associated with mortality [37]. Conversely, sepsis survivors with preexisting diabetes had a higher long-term risk of major cardiovascular events and increased mortality [38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a large Chinese nationwide population-based cohort study showed that patients with T2DM more frequently develop acute kidney injury (AKI) and require renal replacement therapy (RRT), but this was not associated with mortality [37]. Conversely, sepsis survivors with preexisting diabetes had a higher long-term risk of major cardiovascular events and increased mortality [38].…”
Section: Discussionmentioning
confidence: 99%
“…31 This significant mortality is attributed to recurrent hospitalizations as well as an increase in cardiovascular disease, particularly with patients with pre-existing diabetes. [32][33][34] Providing patients and their families with a short-and long-term mortality and morbidity prognosis will aid in endof-life decision making. It also provides clinicians with a reason to monitor inflammatory and thrombotic markers for the sickest septic patients.…”
Section: Sepsis Prognosismentioning
confidence: 99%